Robot‐Assisted Simple Prostatectomy for Two Cases of Benign Prostatic Hyperplasia: The First Report in Japan - Hiroyuki Kitano; Hayato Yoshioka; Yuto Ono; Rei Ueno; Yoshinori Nakano; Tomoya Hatayama; Kazuma Yukihiro; Kyosuke Iwane; Yuki Kohada; Miki Naito; Kohei Kobatake; Yohei Sekino; et al. (IJU Case Reports)
ABSTRACT Introduction Robot‐assisted simple prostatectomy is associated with better perioperative outcomes than those of open simple prostatectomy. We report the outcomes of two cases treated with robot‐assisted simple prostatectomy. Case Presentation The first patient was an 81‐year‐old man with a prostate volume of 139 mL. The second patient was a 77‐year‐old man with a prostate volume of 98 mL. Robot‐assisted simple prostatectomy was performed using Da Vinci Xi. The operative times and enucleated weights for the first and second patients were 210 min and 82 g, and 191 min and 53 g, respectively. Postoperative uroflowmetry of the first and second patients revealed maximum flow rates and postvoid residual volumes of 32.5 mL/s and 15 mL at 6 months postoperatively, and 22.1 mL/s and 6 mL at 1 month postoperatively, respectively. Conclusion Robot‐assisted simple prostatectomy is useful for large prostates.